Biomechanics of competitive swimming strokes - Barbosa, T. M.; Marinho, D. A.; Costa, M. J.; Silva, A. J. (Biomechanics in applications, 2011)
The aim of this chapter has two folds: (i): to perform a biomechanical characterization of the four competitive swimming strokes, based on the kinematics, kinetics and neuromuscular analysis; (ii) to report the relationships established between all the domains and how it might influence the swimming performance